Democracy and Markets: The Case of Exchange Rates - John R. Freeman; Jude C. Hays; Helmut Stix (Oesterreichische Nationalbank (OeNB), 1999)
The relationships between the workings of democratic institutions and currency markets are studied. Several competing propositions about how political (re)equilibration affects currency markets are derived and tested. The results support the view that democratic politics affects currency markets. Expectations and uncertainty about electoral outcomes and government survival affect the probability of switching between currency market equilibria. Additionally, opinion polls about chief executive performance have a direct effect on the probabilities of switches between currency regimes suggesting that these polls cause currency traders to revise their expectations about the stability of governments and (or) the contents of public policies. Electoral institutions mitigate the impact of politics on currency market equilibria. Political effects are weaker in countries with proportional representation electoral systems than in countries with majority-plurality systems. There is less evidence that central bank independence, consensual-corporatist systems, or "political coherency" reduces the effect of politics on currency markets.
Keywords: 330